Prevalence trends of wood use as the main cooking fuel in Mexico, 1990-2013 - Eduardo Hernández-Garduño; Eva Gómez-García; Saúl Campos-Gómez (Instituto Nacional de Salud Pública, 2017)
Objective. To determine prevalence trends of using Wood as the Main Cooking Fuel (WMCF) in Mexico and household characteristics that predict its use. Materials and methods. Estimates were obtained from the 1990, 2000 and 2010 censuses and from a national survey performed in 2012 and 2013. Results. In 2012-2013, 9.5% of the 66 321 surveyed households and 10.9% of their 252 011 residents used WMCF. Prevalence was higher in rural (40.5%) than urban areas (1.5%), p<0.0001. From 1990 to 2013 wood use decreased by 53% overall and by 28.6% in rural areas, gas use increased respectively by 17.5 and 52.7%. Predictors of using WMCF were living in rural or suburban areas and those associated with low socioeconomic status. Conclusion. Use of WMCF has decreased substantially in Mexico but at a slower pace in rural areas. Improving household characteristics and socioeconomic status may decrease use of WMCF at a higher rate.